The effect of YouTube videos with immersive learning strategy on young learner speaking performances (Englisia : Journal of Language, Education, and Humanities, 2025)
This study seeks to evaluate the impact of YouTube videos incorporating an immersive learning strategy on the speaking performance of young learners. It is designed as a quantitative research project. The participants consist of all fifth-grade students at Islamic Primary School 6 Banda Aceh during the 2023/2024 academic year, totaling 40 students—20 engaged in pair learning and 20 in individual learning. A random sampling method was implemented using Google Forms. Data collection involved an oral pre-test and post-test or interview as the primary instrument. The data were analyzed statistically with the Wilcoxon signed-rank test to determine the p-value for four speaking skills. The results revealed a sig 2-tailed value of 0.000 for all four items, falling below the 0.05 significance level. This indicates that YouTube videos with an immersive learning strategy significantly influenced the speaking performance of young learners, particularly in expressing personal needs. These findings carry pedagogical implications for EFL teachers, encouraging the use of YouTube videos to improve students’ speaking abilities. The results can guide teachers and curriculum designers in choosing and organizing learning activities to optimize language development outcomes through a student-centered approach.
Keywords: Immersive Learning Strategy; YouTube video; speaking; individual learning; pair learning